Investigation of the Erosion Mechanism of the Mold Flux Containing Rare Earth Oxide on the Submerged Entry Nozzle Affected by an External Electric Field. Issue 11 (18th August 2022) - Tian, Chen; Yuan, Lei; Wen, Tianpeng; Yu, Jingkun; Liu, Guoqi; Li, Hongxia
Abstract : Considering the change and unpredictability of the mold flux containing rare earth oxides, the impact of controlling the erosion behavior of the mold flux containing rare earth oxide on the submerged entry nozzle is thoroughly investigated herein by applying an electric field. The extracted results show that the rare earth is reduced, and Ce 3+ ions and compounds are formed. Under the control of electrochemical reaction in the negative enforced electric field, a stable and dense protective film with a multilayer structure is formed on the surface of the electrode. The existence of this film can effectively prevent the erosion of the submerged entry nozzle. In addition, the phase composition of the mold flux is not affected by the externally applied electric field. The implementation of the external electric field is anticipated to be used as a new method for the high‐quality and high‐efficiency continuous casting production of rare earth steel. Abstract : The dissolution and erosion behavior of slag line can be controlled by incorporating interfacial electrochemical reactions under the negative electric field. The external electric field may be used as a new method for the high‐quality and high‐efficiency continuous casting production of rare earth steel.